IMPLEMENTASI AROMATERAPI PAPPERMINT UNTUK MENURUNKAN KEJADIAN MUAL DAN MUNTAH PADA PASIEN PASCA OPERASI DENGAN ANESTESI UMUM DI RSUD DR M. ASHARI PEMALANG - Masruroh, Masruroh; Roro Lintang Suryani; Danang Tri Yudono (Bajang Institute, 2024)
PONV is nausea and vomiting that occurs after surgery and before the patient goes home from the hospital. Efforts to reduce the incidence of postoperative nausea and vomiting can be done by using several strategies for preventing and treating nausea and vomiting, either with pharmacological or non-pharmacological therapy (aromatherapy, acupuncture, acupressure, relaxation therapy, hypnotic therapy, and music therapy). Objective: The PKM activity aims to implement peppermint aromatherapy to reduce the incidence of nausea and vomiting in post-operative patients under general anesthesia. Method: This PKM method is carried out by providing peppermint aromatherapy by using 3 drops of peppermint aromatherapy oil on a cotton ball and then asking the respondent to inhale it for 5 minutes. After 5 minutes, respondents were asked to take another nausea scale measurement. After that, the patient is invited to take anti-nausea medication if the nausea does not decrease. Result: The results obtained from this activity are that peppermint aromatherapy can reduce the intensity of the patient's nausea and vomiting and reduce the use of pharmacological therapy by switching them to non-pharmacological therapy, namely peppermint aromatherapy. Conclusion: The output obtained from this PKM activity is that partners can develop non-pharmacological therapeutic health services using peppermint aromatherapy as an intervention in reducing the intensity of nausea and vomiting in post-operative patients under general anesthesia. It is hoped that this PKM activity can become a reference for the community in dealing with nausea and vomiting using non-pharmacological therapy